دراسة بتروغرافية للصخور البازلتية في السفرقية في شمال غرب سورية (Latakia University Journal -Basic Sciences Series, 2017)
تتميز الصخور البازلتية في موقع السفرقية (منطقة القرداحة ) بتماسكها ومقاومتها وتتألف من الأسفل الى الأعلى طف بازلتي بركاني شديد الفساد وبازلت فراغي متوسط القساوة إلى قاسي (رمادي) وتحوي الفراغات في أغلبها نواتج التجوية مواد غضارية وكلسيه يليه بازلت كتلي مصمت ذو قساوة عالية له بنية بلورية ناعمة - رمادي مسود .يتكون البازلت بتروغرافياً في هذا الموقع من بازلت أوليفيني مصمت، بازلت أوليفيني فراغي، بازلت أوليفيني أوجيتي مصمت، بازلت أوليفيني –بلاجيوكلازي، بازلت أوليفيني أوجيتي مصمت، بازلت أوليفيني أوجيتي فراغي، بازلت، بازلت بلاجيوكلازي فقط في الشريحة S14.وصخور بيروكلاستية: لابيل أوليفيني مصمت-لابيل أوليفيني – بلاجيوكلازي – لابيل بازلت أوليفيني-أوجيتي.Field study of the basalt rocks indicate in Jaubet-AL Dilbe that casts basalt in the field consist of tuffit, pyroclastic Sometimes consist of porphyric coarsebasalt with lava structure and brescia of tufa ,which contain a lot of surrounding rocks as lime stone and dolomite. The basalt mass noting the presence of dykes in search area incisor squad pyroclastic. The basalt color is light gray to dark gray. It is form the following petrographical kinds: olivine basalt, olivine augite basalt, olivine plagioclase basalt, plagioclase basalt. As for the lapilli consist of basalt (olivine basalt olivine vascular basalt and plagioclase basalt)